Aviation Safety Management: Minimizing the Deleterious Effect of an Aviation Disaster - Hafiza Zainudin, Ainul; Akhmal Hasmin, Nor; Waseem Dhihny, Ahmad; Mohd Shah, Rohani (International Journal of Engineering and Technology, 2018)
Safety management of civil aviation industry should be taken assiduously to preserve incalculable human life. Though a comprehensive regulatory framework on safety management has been established at a local and international level to improve the safety standard in the aviation industry, this century has witnessed a rapid increased of aviation disasters due to the continued growth of safety mismanagement. This paper offers a discussion of the risk factor as an essential safety tool in preventing aviation disaster through its compliance with safety regulation and safety standard imposed upon regulatory authority. This paper also intends to discuss the safety doctrine laid down in Integrated Emergency Management Model (IEMM) and Chaos Theory in managing aviation disaster. This paper also tenders a discussion on the current legal position concerning safety management adopted by Malaysian aviation authorities. The reference is made to the State Safety Program (SSP) and Safety Management System (SMS) under Annex 19 of Chicago Convention within the purview of International Civil Aviation Organization (ICAO). The methodology used is the doctrinal research methodology in the discipline of law. The findings of this study serve to validate that Malaysia to the full extent have implemented ICAO Safety Management Manual (SMM); nevertheless, the effectiveness is debatable. Based on the literature, this paper seeks to propose that IEMM and Chaos Theory be made the foundation in establishing Malaysia's regulatory framework and the synchronisation between domestic law and international convention to be made mandatory.Â Â